Infección Tuberculosa Latente En Trabajadores De La Salud (2023)
Latent tuberculosis infection is defined as the immune response to Mycobacterium tuberculosis without clinical manifestations. Health workers carry out their work activities in services where there are occupational risk factors, such as the presence of patients infected with tuberculosis, health workers with infectious tuberculosis, work environments with lack of ventilation and lighting, among others.